Perang total dan mobilisasi sumber daya nasional dalam Perang Dunia II: Pembelajaran strategis bagi ketahanan nasional Indonesia - Widjayanto, Joni; Susetyo, Eko; Ghazalie, Ghazalie; Leonardo, Vande (Universitas Negeri Malang, 2025)
Total war and the mobilization of national resources during World War II: Strategic insights for Indonesia’s national resilience This study highlights the importance of transforming Indonesia's national resilience in the face of contemporary threats such as cyberattacks, disinformation, ecological disasters, and geopolitical dynamics. Employing a qualitative approach with an intrinsic case study design, data were collected through policy analysis, interviews, and participatory observation. The findings reveal institutional fragmentation, weak intersectoral coordination, limited public participation, and threat literacy. The study proposes a conceptual model of national resilience comprising five dimensions: institutional structure, sectoral integration, adaptive capacity, public awareness, and geopolitical orientation. It emphasizes that without synergy among these elements, the resilience system remains vulnerable. Therefore, a new paradigm is needed more adaptive and participatory focusing on institutional reform, community empowerment, and a sharper geopolitical strategy in the Indo-Pacific region. Penelitian ini menyoroti pentingnya transformasi ketahanan nasional Indonesia dalam menghadapi ancaman kontemporer seperti serangan siber, disinformasi, bencana ekologis, dan dinamika geopolitik. Menggunakan pendekatan kualitatif dengan desain studi kasus intrinsik, data dikumpulkan melalui analisis kebijakan, wawancara, dan observasi partisipatif. Hasil menunjukkan adanya fragmentasi kelembagaan, lemahnya koordinasi antar sektor, serta minimnya partisipasi masyarakat dan literasi ancaman. Studi ini mengembangkan model konseptual ketahanan nasional yang terdiri atas lima dimensi: struktur kelembagaan, integrasi sektor, kapasitas adaptif, kesadaran masyarakat, dan orientasi geopolitik. Ditekankan bahwa tanpa sinergi antar elemen tersebut, sistem ketahanan akan tetap rentan. Oleh karena itu, dibutuhkan paradigma baru yang lebih adaptif dan partisipatif, dengan fokus pada reformasi institusional, penguatan peran masyarakat, dan strategi geopolitik yang lebih tajam di kawasan Indo-Pasifik.